Hubungan Komunikasi SBAR Saat Serah Terima dengan Kinerja Perawat dalam Pemberian Asuhan Keperawatan - Chania Sofiatur Muzzayanah; Dyah Wiji Puspita Sari; Retno Issroviatiningrum (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Disruption of the treatment process, lack of attention, and lack of knowledge about how to obtain medical information about the patient result in poor communication. Optimizing the role and function of nurses, especially independent care, can increase the professionalism of nurses in this hospital, which can be achieved through effective communication between nurses and other health service providers. The purpose of this research is to determine the relationship between SBAR communication and employee work habits when carrying out maintenance tasks at the Sultan Agung Islamic House, Semarang. This research is a quantitative study using a cross-sectional design. Data collection was carried out using questionnaires and observation sheets for 50 respondents. This study used a total sampling approach, and Spearman's rank correlation test was applied for statistical analysis. The results of the Spearman rank test of SBAR communication data during handover and the performance of nurses in providing nursing care obtained a p value of 0.003 (<0.05), which means that Ha is accepted or there is a relationship, with the relationship being quite strong (0.406) and the direction is positive. To increase effectiveness in providing nursing care in hospitals, nurses are required to be able to implement SBAR communication more effectively during handover.